Complement C4-deficient mice have a high mortality rate during PTZ-induced epileptic seizures, which correlates with cognitive problems and the deficiency in the expression of Egr1 and other immediate early genes - Veremeyko, Tatyana; Jiang, Rongcai; He, Mingliang; Ponomarev, Eugene D. (Frontiers in Cellular Neuroscience, 2023)
Complement system plays an important role in the immune defense against pathogens; however recent studies demonstrated an important role of complement subunits C1q, C4, and C3 in normal functions of the central nervous system (CNS) such as non-functional synapse elimination (synapse pruning), and during various neurologic pathologies. Humans have two forms of C4 protein encoded by C4A and C4B genes that share 99.5% homology, while mice have only one C4B gene that is functionally active in the complement cascade. Overexpression of the human C4A gene was shown to contribute to the development of schizophrenia by mediating extensive synapse pruning through the activation C1q-С4-C3 pathway, while C4B deficiency or low levels of C4B expression were shown to relate to the development of schizophrenia and autism spectrum disorders possibly via other mechanisms not related to synapse elimination. To investigate the potential role of C4B in neuronal functions not related to synapse pruning, we compared wildtype (WT) mice with C3- and C4B- deficient animals for their susceptibility to pentylenetetrazole (PTZ)- induced epileptic seizures. We found that C4B (but not C3) – deficient mice were highly susceptible to convulsant and subconvulsant doses of PTZ when compared to WT controls. Further gene expression analysis revealed that in contrast to WT or C3-deficient animals, C4B-deficient mice failed to upregulate expressions of multiple immediate early genes (IEGs) Egrs1-4, c-Fos, c-Jus, FosB, Npas4, and Nur77 during epileptic seizures. Moreover, C4B-deficient mice had low levels of baseline expression of Egr1 on mRNA and protein levels, which was correlated with the cognitive problems of these animals. C4-deficient animals also failed to upregulate several genes downstream of IEGs such as BDNF and pro-inflammatory cytokines IL-1β, IL-6, and TNF. Taken together, our study demonstrates a new role of C4B in the regulation of expression of IEGs and their downstream targets during CNS insults such as epileptic seizures.